Upaya Mengembalikan Produktivitas Dakwah dan Semangat Belajar Muslimah Lombok Timur di Akhir Pandemi Covid-19 - Sri Ujiana Putri (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2023)
Islam makes da'wah an obligation because by means of da'wah, Islam can reach people across generations and across eras. The aim of this research is to find out the productivity of Muslim women's da'wah and enthusiasm for learning at the end of the pandemic, especially in East Lombok. This research is qualitative research with a sociological approach. The research results show that the pandemic which lasted almost two years did not reduce the enthusiasm of students to carry out their work programs offline. This is also supported by the enthusiasm and enthusiasm of Muslim women and children in East Lombok to take part in activities held by STIBA Makassar KKN students. The work programs implemented include kindergarten teaching, TPA teaching, social service, Tablig Akbar specifically for Muslim women and the Pious Children's Festival.